Impact of Bank Credit on Green Total Factor Productivity of Private Enterprises: Microanalysis from China - Jin, Huanhuan; Deng, Huarong; Xu, Dongyu; Zhang, Zhouyi (Transformations In Business & Economics, 2025)
The transformation and upgrading of private enterprises require significant financing. Overcoming this financing dilemma is key for private enterprises to achieve high-quality development. Green total factor productivity (GTFP) considers the quality of economic growth and environmental responsibility and is an important symbol of enterprises’ high-quality development. From the credit perspective, this study reveals the mechanism by which bank credit influences the GTFP of private enterprises. The main conclusions are as follows: (1) The benchmark regression results show that bank credit can promote the improvement of the GTFP of private enterprises; (2) The mechanism test shows that hard technology acts as an intermediary, i.e., bank credit promotes the progress of hard technology, thereby improving the GTFP of private enterprises; (3) The moderating effect analysis shows that credit discrimination can weaken the promoting effect of bank credit on the GTFP of private enterprises. However, this effect is related to the size of enterprises. This study is conducive to further understanding the relationship between bank credit and private enterprises from a microperspective. Moreover, this study provides empirical evidence to promote high-quality economic development.